Pemberdayaan Ibu Hamil dan Ibu Balita Dalam Upaya Pencegahan Malaria Melalui Pendekatan Promotif dan Preventif di Wilayah Kerja Puskesmas Biak Kota Kabupaten Biak Numfor - Selina Boseren; Hermayani; Annisa Anggraini (Rena Cipta Mandiri, 2025)
Malaria in Indonesia remains a major public health concern in the eastern regions, despite a national decline in prevalence. An analysis of partner data obtained for 2024 indicates that approximately 93% of districts/cities in Indonesia have become malaria-free; however, Papua and West Papua still account for over 60% of national cases. In Papua Province, malaria is classified as highly endemic, with an Annual Parasite Incidence (API) reaching 12.5 per 1,000 population. Pregnant women constitute a vulnerable group due to limited access to antenatal care services and low use of insecticide-treated bed nets. Biak Numfor District is categorized as moderately endemic, with an API of 4.2 per 1,000 population and approximately 1,850 malaria cases throughout 2024, including 210 cases affecting pregnant women. Key risk factors include tropical conditions, population mobility and insufficient health education. Within the service area of Biak Kota Health Center, approximately 280 malaria cases were recorded in 2024, including 35 cases among pregnant women. The objective of this community service activity is to enhance the knowledge of pregnant women and mothers of toddlers within the Biak Kota Health Center’s service area regarding malaria, including its transmission routes, impacts on pregnancy, causes, symptoms, and consequences of malaria during pregnancy (such as anemia, miscarriage, and low birth weight), prevention methods through the use of long-lasting insecticidal nets (LLINs), maintaining environmental cleanliness, and avoiding mosquito bites, as well as the importance of routine blood testing for malaria during antenatal care (ANC) visits. The method employed involved small group discussions using leaflet.